"Concrete ways we can make a difference": A multi-centre, multi-professional evaluation of sustainability in quality improvement education. (3rd October 2022) - Spooner, Rosanna; Stanford, Victoria; Parslow-Williams, Siobhan; Mortimer, Frances; Leedham-Green, Kathleen
Abstract: Quality improvement (QI) projects are a mandatory part of postgraduate medical training in the UK and graduating medical students must be competent in QI theory. We evaluated an educational toolkit that links concepts of sustainable healthcare with established quality improvement methodologies (the SusQI approach, available at www.susqi.org ). The SusQI approach was implemented across a range of undergraduate and postgraduate nursing and medical education contexts. Educational strategies included guided online learning, live interactive webinars, small group activities and scaffolded project work. The evaluation strategy was informed by theories of academic motivation, educational value within communities of practice and behaviour change. A simultaneous nested design was tested using a mixed methods survey with input from learners and teachers. 177 survey responses were analysed to quantify and compare self-rated impacts of teaching across different audiences. Qualitative data were inductively coded into themes that were categorised according to above theoretical frameworks. Participants felt that this was 'time well spent' and many described transformative impacts that guided their daily professional practice beyond learning about QI. We suggest that meaningful space is found within both undergraduate and postgraduate healthcare curricula for SusQI, as a way of engaging and motivating learners to contribute to the creation of a sustainable healthcare system.